Mindset Nano Tips to Shift from Survival to Thriving in Complex Situations with Gemma Leigh Roberts. - Gemma Leigh Roberts, Dr (linkedin.com, 2024)
Discover how to reset your mindset to thrive in complex situations. Each video is less than three minutes long, so you can make learning fit into even your busiest days.